Environmental Policy in the EU Actors, Institutions and Processes (Taylor & Francis, 2021)
The European Union (EU) has a hugely important effect on the way in which environmental policies are framed, designed and implemented in many parts of the world, but especially Europe. The new edition of this leading textbook provides a state-of-the-art analysis of the EU's environmental policies. Comprising five parts, Environmental Policy in the EU covers the rapidly changing context in which EU environmental policies are made, the key actors who interact to co-produce them and the most salient dynamics of policy making, ranging from agenda setting and decision making, through to implementation and evaluation. Written by leading international experts, individual chapters examine how the EU is responding to a multitude of different challenges, including biodiversity loss, climate change, energy insecurity, and water and air pollution. They tease out the different ways in which the EU's policies on these topics co-evolve with national and international environmental policies. In this systematically updated fourth edition, a wider array of learning features are employed to ensure that readers fully understand how EU environmental policies have developed over the last 50 years and how they are currently adapting to the rapidly evolving challenges of the twenty-first century, including the COVID-19 pandemic. It is an essential resource for undergraduate and postgraduate students studying environmental policy and politics, climate change, environmental law and EU politics more broadly.
English
Keywords: Environmental policy & protocols; EU; environmental policies